The effect of grazing intensity and supplementation on performance, stress indicators and metabolic profiles of finishing lambs - Ramos Costa, Joao Paulo [UNESP]; Silva, Wilton Ladeira da [UNESP]; Paula, Gregory Caputti de [UNESP]; Tsuzukibashi, Denise [UNESP]; Malheiros, Euclides Braga; Ruggieri, Ana Claudia; Negrao, Joao Alberto (Univ Estadual Londrina, 2015)
In the present study, the effect of grazing intensity (GI) and feed supplementation in sixty-four crossbred Santa Ines lambs was assessed based on performance, blood stress indicators, and metabolic profiles. The GIs analyzed were VH = very high, H = high, L = low, and VL = very low, and were represented by the residual leaf area index (LAIr). The lambs were divided into two groups, supplemented (SP) and non-supplemented (NSP). The dry matter intake (DMI) and average daily gain (ADG) increased linearly with decreasing GI (P < 0.05), and the ADG was higher for the NSP group than the SP group (P < 0.05). The plasma cortisol concentration was higher in the NSP group (P < 0.05), and it was not affected by GIs (P > 0.05). The neutrophil: lymphocyte (N:L) ratio decreased linearly with GI (P < 0.05), and the SP group had a higher N: L ratio (P < 0.05). None of the parameters evaluated for protein metabolism were affected by GI (P > 0.05), except albumin, where the SP group had a higher concentration of this metabolite (P < 0.05). Regarding energy metabolism indicators, glucose showed a linear increase with a decrease in GI (P < 0.05) and was higher in the SP group (P < 0.05); however, there was a decreasing linear effect (P < 0.05) and the NSP group had higher serum levels (P < 0.05) of non-esterified fatty acids (NEFA). The concentration of beta hydroxybutyrate (HBA-B) was higher in the SP group (P < 0.05). The concentration of calcium was affected by GI (P < 0.05). The phosphorus concentration was higher in the SP group (P < 0.05), and concentration of magnesium was not affected by any of the treatments (P > 0.05). It was concluded that GI and SP modified the performance, stress indicators, and metabolic profiles of finishing lambs.
Keywords: Blood parameters; cortisol; energy metabolism; ovine; pasture; protein metabolism